Metallic materials from the Rocchetta di Airuno (LC) from the fortuitous discovery to the preliminary investigation (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This contribution aims to focus attention on the discovery of some metallic materials that took place near the sanctuary of “Madonna della Rocchetta” of Airuno in the Province of Lecco. The reporting of these arrived in December 2016 to the then Soprintendenza per i beni archeologici della Lombardia, their subsequent recovery and delivery to the Soprintendenza's warehouses, allowed to develop the following preliminary investigation.
Keywords: Middle Ages; Discovery; Metallic; Lombardy; Lecco; Small finds